Home production technology and time allocation: Empirics, theory, and implications - Lei Fang; Guozhong Zhu (Federal Reserve Bank of Atlanta, 2012)
We document a set of time use patterns in both time series and cross sections. To explain these facts, we propose and estimate a model of time allocation that emphasizes the role of home production technology. We find it necessary to consider both labor-augmenting technology and total factor productivity in home production. Based on the estimated model, we study the effects of proportional tax and lump-sum transfer on time allocation and labor supply, with the roles of home production technology and wage heterogeneity highlighted.
Keywords: J22; J24; 330; time allocation; home production; technology